2021
DOI: 10.1021/acs.jafc.1c00136
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 5,7-Methoxyflavones by Selected Entomopathogenic Filamentous Fungi

Abstract: 5,7-Dimethoxyflavone, a chrysin derivative, occurs in many plants and shows very low toxicity, even at high doses. On the basis of this phenomenon, we biotransformed a series of methoxy-derivatives of chrysin, apigenin, and tricetin obtained by chemical synthesis. We used entomopathogenic fungal strains with the confirmed ability of simultaneous hydroxylation/demethylation and glycosylation of flavonoid compounds. Both the amount and the place of attachment of the methoxy group influenced the biotransformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
(128 reference statements)
1
8
0
Order By: Relevance
“…The obvious difference was the C-4′ chemical shift of 5, which was downfield than 1 . The data were also compared with 3′- O - β -D-(4″- O -methylglucopyranosylo)-5, 7, 4′, 5′-tetramethoxylavonone [ 10 ], except for the presence of sugar at C-3′. The HMBC correlation from H-1″ to C-3′ ( Figure 3 ) indicated glucose substitution.…”
Section: Resultsmentioning
confidence: 99%
“…The obvious difference was the C-4′ chemical shift of 5, which was downfield than 1 . The data were also compared with 3′- O - β -D-(4″- O -methylglucopyranosylo)-5, 7, 4′, 5′-tetramethoxylavonone [ 10 ], except for the presence of sugar at C-3′. The HMBC correlation from H-1″ to C-3′ ( Figure 3 ) indicated glucose substitution.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of Isaria farinosa strains to hydroxylate and 4-O-methylglycosylate flavonoid compounds was also described [18][19][20]. In our previous work, we also observed that they perform demethylation and then 4-O-methylglycosylation of methoxyflavones [19,21].…”
Section: Introductionmentioning
confidence: 68%
“…At the same time, the extensive application of filamentous fungi in biotransformation has attracted much attention. 41 In order to find more strains for biotransformation of natural products and enrich the microbial strain library, we try to obtain filamentous fungi from common sources in daily life. The results showed that C. cladosporioides (Figure 2) derived from moldy food had an excellent biotransformation effect on PA.…”
Section: Resultsmentioning
confidence: 99%